High molecular weight hyaluronic acid reduces the growth and biofilm formation of the oral pathogen Porphyromonas gingivalis - Meshal S. Alharbi; Fahad A. Alshehri; Ahmed S. Alobaidi; Raed Alrowis; Nouf Alshibani; Abdurahman A. Niazy (Elsevier, 2023)
Background: Porphyromonas gingivalis (P. gingivalis) is viewed as a keystone microorganism in the pathogenesis of periodontal and peri-implant diseases. Hyaluronic acid (HA) is believed to exert antimicrobial activity. The aim of this study is to assess the in-vitro growth and biofilm formation of P. gingivalis under HA and compare the effect of HA to that of azithromycin (AZM) and chlorhexidine (CHX). Materials and methods: In each material, the minimum inhibitory concentration (MIC), 50% MIC, 25% MIC, and 12.5% MIC were tested. The growth of P. gingivalis was evaluated by absorbance spectrophotometry after 48 h. A biofilm inhibition assay was performed on a 72-hour culture by washing planktonic bacterial cells, fixing and staining adherent cells, and measuring the variation in stain concentrations relative to the untreated control using absorbance spectrophotometry. Results: The results show that the overall growth of P. gingivalis after 48 h was 0.048 ± 0.030, 0.008 ± 0.013, and 0.073 ± 0.071 under HA, AZM, and CHX, respectively, while the untreated control reached 0.236 ± 0.039. HA was also able to significantly reduce the biofilm formation of P. gingivalis by 64.30 % ± 22.39, while AZM and CHX reduced biofilm formation by 91.16 %±12.58 and 88.35 %±17.11, respectively. Conclusions: High molecular-weight HA significantly inhibited the growth of P. gingivalis. The overall effect of HA on the growth of P. gingivalis was similar to that of CHX but less than that of AZM. HA was also able to significantly reduce the biofilm formation of P. gingivalis. However, the ability of HA to prevent the biofilm formation of P. gingivalis was generally less than that of both AZM and CHX.